Предмет: Алгебра,
автор: Хэймзон
решить уравнение x2*(x+1)-(x+2)*(2x-3)=x2*(x-1)
Ответы
Автор ответа:
0
x³+x²-(2x²-3x+4x-6)-x³+x²=0
x²-2x²+3x-4x+6+x²=0
-x+6=0
x=6
x²-2x²+3x-4x+6+x²=0
-x+6=0
x=6
Автор ответа:
0
печему + x^2 в конце? если там - и откуда 0 ??
Автор ответа:
0
x^2(x-1)=x^3-x^2
Автор ответа:
0
перенесли все в левую часть.
Автор ответа:
0
ок
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: 5uperminecraft801
Предмет: Другие предметы,
автор: memasiki2003
Предмет: Алгебра,
автор: lena19992304
Предмет: Алгебра,
автор: grishinayfnfkb